Prevalence of parafunctional oral habits in 12-13 years adolescents - Maritania Balleuxs Pereira; Lian Cristino Nuñez Peña; Yurima Trupman Hernández; Lidia Beatriz Caraballo Villalón (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Parafunctional oral habits are the primary or secondary cause of malocclusions or dentomaxillofacial anomalies which severity varies depending on age. Objective: To determine the prevalence of parafunctional oral habits in 12-13 years adolescents. Methods: An observational, descriptive and cross-sectional study was carried out in 450 adolescents that presented a permanent complete teething according to their age, belonging to Manuel Ascunce Domenech Secondary School of Guantánamo province, who were assisted in the Stomatologic Clinic of 4 de Abril Teaching Polyclinic in that city from December, 2022 to January, 2023. The selected variables were sex, age, as well as the presence and type of parafunctional habit. The chi-square test was used with a significance level α=0.05. Results: The prevalence of parafunctional oral habits was 38.0%; of these, the most frequent were queilophagia (33.9%) and mouth breathing (25.2%), mainly in women (50.3%) and the 12 years group (62.6%). Conclusions: A low prevalence of parafunctional oral habits was found in 12-13 years adolescents and queilophagia was the most significant.